RETRACTED ARTICLE: Serum bilirubin levels in primary Sjögren’s syndrome: an association with interstitial lung disease - You-Fan Peng; Fei-Yan Lu; Li-Ya Ma (BMC Pulmonary Medicine, 2023)
Abstract Objective We aimed to assess the association between serum bilirubin levels and interstitial lung disease (ILD) in patients with Primary Sjögren’s syndrome (pSS). Materials and methods The retrospectively analysis included 89 consecutive patients with pSS, we collected the clinical materials of pSS patients from the electronic medical records, and all pSS patients were divide into pSS with ILD group and pSS without ILD group. Results Serum bilirubin levels were significantly lower in pSS patients with ILD than those without ILD (p = 0.010). Serum bilirubin levels showed a significant negative correlation with erythrocyte sedimentation rate (ESR) (r = -0.321, p = 0.002) in patients with pSS. A multivariable logistic regression analysis confirmed that serum bilirubin presented an independent association with ILD in patients with pSS (OR = 0.841, 95%CI:0.728–0.972, p = 0.019). Conclusion Serum bilirubin is independently associated with ILD and therefore may be a promising marker of ILD in patients with pSS.